P524 Administration and monitoring of biologic therapy in patients with inflammatory bowel disease: A national Danish survey. (15th January 2020) - Volmar, S; Wildt, S; Munck, L K
Abstract: Background: Administration and monitoring of biologic therapy to patients with inflammatory bowel disease (IBD) is an increasing burden in gastroenterology outpatient clinics. The aim of this study was to compare the present organisation of biologic therapy to IBD patients in Denmark with the published evidence. Methods: A national online survey using SurveyXact was send to all outpatient clinics administering biologic treatment to IBD patients in Denmark in March 2019. It focused on infusion time, post infusion observation and biochemical control of treatment with biologic drugs. A systematic literature search covering the same topics was performed on PubMed in May 2019. Results: 21 of 23 clinics completed the survey. Infusion time for infliximab induction was 2 h in all clinics and was reduced to 30 min or 1 h in 60 % and 40% of clinics respectively after ≥ 10 infusions. Vedolizumab infusion time was 30 min in 90% of clinics from start. Ustekinumab infusion time was 1 h in 90% of clinics. Observation time after intravenously administered biologics varied considerably. Only half of the clinics discharged patients on infliximab without post-infusion observation from the start of maintenance treatment increasing to 80% of clinics after ten infusions. About half of the clinics observed patient on vedolizumab maintenance for at least 30 min after 5 infusions. Ten clinics discharged patients immediately after the initial ustekinumab infusion. In 30–60% of clinics, patients were observed 20–120 min after subcutaneous injection of ustekinumab, adalimumab or golimumab. Twenty clinics controlled laboratory parameters prior to every maintenance treatment with infliximab and vedolizumab, no matter of infusion interval, while patients on injection therapy with adalimumab, golimumab and ustekinumab had biochemical tests taken every second to third months. Only two clinics measured trough values and antibodies against biologics routinely and adjusted the dose accordingly to the trough value. The systematic literature search identified 26 relevant articles. These showed that infliximab infusion time of 30 minutes is safe and questioned the necessity of post-infusion observation. There was no consensus on the frequency of biochemical control in patients on biologics. Conclusion: Reduction and harmonisation of infusion time, post-infusion and post-injection observation time for patients on biologics could release patient and staff resources.